Strategy to Build Competitive Advantage of Islamic Higher Education at an University in Surabaya: Strategi Membangun Keunggulan Kompetitif Perguruan Tinggi Islam di Sebuah Universitas di Surabaya - Mochammad Danu Kurniadi; Biyanto Biyanto (Academia Open, 2022)
This study aims to reveal and analyze the strategies used by STAI Ali bin Abi Talib to build a competitive advantage and how to develop its advantages in order to become a sustainable advantage. This research is a field research with a qualitative descriptive approach. The research results obtained are (1) Ali bin Abi Talib's STAI strategy in building competitive advantage is to formulate a curriculum that combines the national curriculum and international curriculum in modern Arabic learning, prepare competent human resources, and create a learning environment with boarding schools; (2) The competitive advantage development program owned by STAI Ali bin Abi Talib is to evaluate and develop a curriculum according to the needs of the times and the demands of the government, improve the quality of human resources with programs for developing academic competence and spiritual competence of lecturers, develop a boarding system with additional infrastructure and various programs to develop the talents and interests of students.